Performance of Finisher Broilers Fed Wet Mash with or Without Drinking Water During Wet Season in the Tropics - Awojobi, H.A.; Oluwole, B.O.; Adekunmisi, A.A.; Buraimo, R.A. (International Journal of Poultry Science, 2009)
Finisher broilers were fed conventional dry and wet mash with varying amounts of water addition (1.0, 1.5, 2.0 parts of water to 1 part of feed) with and without drinking water. Feed intake was higher (P<0.05) in all wet-fed groups but one than birds that received the conventional dry mash. Live weight gain and carcass yield was better (P<0.05) in all wet-fed groups than dry mash feeding. However, feed conversion efficiency (FCE) was highest in birds that received 1 part of water to 1 part of feed with drinking water, their result is comparable to those on conventional dry mash feeding and significantly (P<0.05) better than other wet-fed groups. No significant (P>0.05) differences were observed in weights of the liver, spleen, intestine, abdominal fat, proventriculus, full-gizzard and caeca. This study recommends 1 part of water to 1 part of feed with drinking water for finisher broilers when raised on wet mash during wet season in the tropics.